Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1037/0022-006x.57.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Links from emotional distress to adolescent drug use: A path model.

Abstract: Administered anonymous surveys asking about drug use, emotional distress, and peer drug associations to 11th and 12th grade high school students (N = 563). Emotional distress variables accounted for only 4.8% of the variance in drug use. The addition of peer drug associations as a predictor variable increased the variance accounted for to 43.4%. A path model of adolescent drug use based on peer cluster theory was tested using LISREL, and this provided a good fit with the data. As predicted, peer drug associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
126
1
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(148 citation statements)
references
References 16 publications
16
126
1
2
Order By: Relevance
“…However, the few prospective studies of the effects of adolescent internalizing symptoms on substance-use disorders have shown no effects (e.g., Chassin et al, 1999) or have suggested that only certain aspects, such as anger, are the specifi c mechanism of effect (McCreary and Sadava, 1999;Tarter et al, 1995). For example, anger has been theorized to lead to substance use either through poor adaptive coping skills (Wills et al, 1999) or through affi liation with deviant peers (Swaim et al, 1989).…”
Section: Theoretical Mediatorsmentioning
confidence: 99%
“…However, the few prospective studies of the effects of adolescent internalizing symptoms on substance-use disorders have shown no effects (e.g., Chassin et al, 1999) or have suggested that only certain aspects, such as anger, are the specifi c mechanism of effect (McCreary and Sadava, 1999;Tarter et al, 1995). For example, anger has been theorized to lead to substance use either through poor adaptive coping skills (Wills et al, 1999) or through affi liation with deviant peers (Swaim et al, 1989).…”
Section: Theoretical Mediatorsmentioning
confidence: 99%
“…These shared feelings can result in drug use, especially if youth consider this kind of behavior as rebellious and authority-challenging (Oetting & Lynch, 2003). However, Swaim et al (1989) reported that anger exerts both direct and indirect effect on drug use through peer drug association, and that this holds true for both male and female students.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from correlation with drug use, these two personality traits consistently show a correlation with drug using or deviant peers (e.g., Swaim et al, 1989;Yanovitzky, 2005Yanovitzky, , 2006, and the association with drug using peers is one of the strongest risk factors for drug use among adolescents and youth. These findings indicate that there is a possibility that sensation seeking and anger do not contribute to drug use directly, but rather indirectly through association with peers who are drug users.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations